Relações de trabalho doméstico remunerado no Brasil : um estudo sobre empregadas e empregadoras no topo da pirâmide social - Eberhardt, Roberta Presser Potrick (2022)
In the present study, the focus is the analysis of domestic work relations in Brazil in families close to the top of the social pyramid, with the main objective of understanding how the daily relationship between employers and domestic workers takes place after the important legislative and socioeconomic changes that occurred over the last few decades. Therefore, based on an analysis of the literature on the subject, as well as the relevant legislation, domestic work relations in Brazil are analyzed and how they develop in a society as hierarchical as the Brazilian one, passing through issues such as that of citizenship and social stratification. The main methodology used will be a qualitative study carried out through semi-structured interviews, which will allow an indepth analysis of the relationship between domestic employers and their employees. In order to carry out the analyses, employers whose families have a level of income and consumption power that place them close to the top of the social pyramid in Brazil, as well as their respective domestic servants, were interviewed. The field research allowed us to verify that, in addition to any legislative or socioeconomic change, the factors that have contributed to changes in the daily relationships of domestic employment are: educational and generational.